Storm Time Electrified MSTIDs Observed Over Mid‐Latitude North America. Issue 3 (7th March 2023) - Kelley, I. J.; Kunduri, B. S. R.; Baker, J. B. H.; Ruohoniemi, J. M.; Shepherd, S. G.
Abstract: Medium‐scale Traveling Ionospheric Disturbances (MSTIDs) are prominent and ubiquitous features of the mid‐latitude ionosphere, and are observed in Super Dual Auroral Radar Network (SuperDARN) and high‐resolution Global Navigational Satellite Service (GNSS) Total Electron Content (TEC) data. The mechanisms driving these MSTIDs are an open area of research, especially during geomagnetic storms. Previous studies have demonstrated that nightside MSTIDs are associated with an electrodynamic instability mechanism like Perkins, especially during geomagnetically quiet conditions. However, dayside MSTIDs are often associated with atmospheric gravity waves. Very few studies have analyzed the mechanisms driving MSTIDs during strong geomagnetic storms at mid‐latitudes. In this study, we present mid‐latitude MSTIDs observed in de‐trended GNSS TEC data and SuperDARN radars over the North American sector, during a geomagnetic storm (peak Kp reaching 9) on 7–8 September 2017. In SuperDARN, MSTIDs were observed in ionospheric backscatter with Line of Sight (LOS) velocities exceeding 800 m/s. Additionally, radar LOS velocities oscillated with amplitudes reaching ±500 m/s as the MSTIDs passed through the fields‐of‐view. In detrended TEC, these MSTIDs produced perturbations reaching ∼50 percent of background TEC magnitude. The MSTIDs were observed to propagate in the westward/south‐westward direction with a time period of ∼15 min. Projecting de‐trended GNSS TEC data along SuperDARN beams showed that enhancements in TEC were correlated with enhancements in SuperDARN SNR and positive LOS velocities. Finally, SuperDARN LOS velocities systematically switched polarities between the crests and the troughs of the MSTIDs, indicating the presence of polarization electric fields and an electrodynamic instability process during these MSTIDs. Key Points: Medium‐scale Traveling Ionospheric Disturbance (MSTID) signatures were observed in Global Navigational Satellite Service Total Electron Content and Super Dual Auroral Radar Network (SuperDARN) ionospheric backscatter during a strong geomagnetic storm MSTID characteristics were broadly consistent between the data sets, with periods of 10–20 min and phase speeds of ∼800 m/s SuperDARN Line of Sight velocities systematically switched polarities between MSTID crests and troughs, indicating polarization electric fields